Effect of replacing fine aggregate and cement with lateritic soil and palm oil fuel ash (POFA) on compressive and tensile strength of concrete - Adnan, Suraya Hani; Ab Halim, Asyraf Hakim (Penerbit UTHM, 2017)
Concrete is a building material that is widely used since the roman times until present day. It is composed mainly of four parts which are water, fine aggregate, coarse aggregate and cement. Additives and reinforcements are usually included in order to achieve the desired physical properties of the finished material. Due to sustainability concern, researchers have studied the potential materials that can be used as the material replacement in the concrete in order to conserve the natural resources. Based on previous studies, laterite soil is one of the potential materials that can be used as the replacement of fine aggregates in concrete. The availability of laterite soil locally and in abundance is a perfect sample to study as it is cheap and the cost of obtaining it is very low. Other advantages includes lateritic concrete structures have potentially sufficient strength compared to normal concrete (Lasisi & Ogunjimi, 1984). Meanwhile, palm oil fuel ash or commonly known as POFA is one of the agriculture waste produced from the palm oil industries. Based on previous study, it has proved that POFA has the potential to be used as the cement replacement in the concrete due to its pozzolanic characteristic which gives optimum strength with the 30% of cement replacement in which it could increase 10% of normal concrete strength (Neville, 2011). Specifically, this study focused on the effect of replacing fine aggregate and cement with lateritic soils and palm oil fuel ash on the compressive and tensile strength of resulted concrete.